2017
DOI: 10.1111/jonm.12460
|View full text |Cite
|
Sign up to set email alerts
|

Race as a predictor of job satisfaction and turnover in US nurses

Abstract: Nurse managers should endeavour to create a workplace free of discrimination. Efforts to increase the job satisfaction of all nurses are of equal importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 18 publications
4
30
1
2
Order By: Relevance
“…We created indicator variables to control for any potential impacts of race as several studies have found significant effects of race on job satisfaction and intent to leave (e.g. Bartel, 1981; Doede, 2017; Moch, 1980; Sørensen, 2004; Tuch and Martin, 1991). We also used age group as a control variable as age affects factors such as an employee’s job satisfaction and intent to leave (Michaels and Spector, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…We created indicator variables to control for any potential impacts of race as several studies have found significant effects of race on job satisfaction and intent to leave (e.g. Bartel, 1981; Doede, 2017; Moch, 1980; Sørensen, 2004; Tuch and Martin, 1991). We also used age group as a control variable as age affects factors such as an employee’s job satisfaction and intent to leave (Michaels and Spector, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…H5c: Type of industry is a moderator for the effect of job empowerment on turnover intention. Doede (2017) has shown that race can be a predictor of the relationship between job satisfaction and turnover intention. It is suggested that the relationship between job satisfaction and turnover intention can be signifi cantly different in different countries (Huang, 2011;Luu & Hattrup, 2010).…”
Section: Conceptual Relationships and Hypothesis Developmentmentioning
confidence: 99%
“…In the 1990s, the existence of a racist health care system was either denied outright ( Funkhouser & Moser, 1990 ) or “whited-out” ( Jackson, 1993 ) through cultural analyses that attributed health care disparities to individual health behaviors while also attributing careworkers’ experiences of systemic racism to individual bias ( Porter & Barbee, 2004 ). However, ongoing research in the 21st century draws our attention to the ways that race operates as a barrier and an axis of inequality in both nursing education and nursing practice ( Beard & Julion, 2016 ; Byrne, 2001 ; Doede, 2017 ; Gilliss, Powell, & Carter, 2010 ; J. M. Hall & Fields, 2013 ; Hamilton & Haozous, 2017 ; Hassouneh, 2013 ; Lancellotti, 2008 ; Mapedzahama, Rudge, West, & Perron, 2012 ; Moceri, 2012 , 2014 ; Moore & Continelli, 2016 ; Robinson, 2014 ; Schroeder & DiAngelo, 2010 ).…”
Section: Introductionmentioning
confidence: 99%